Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas dan Reputasi KAP terhadap Audit Report Lag (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Ayu Puspaningrum; Amir Indrabudiman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine and analyze influence Firm Size, Profitability, Solvency, and KAP Reputation of the Audit Report Lag of energy sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. In this study, a purposive sampling method is used, which obtained 53 companies. The data analysis used in this study is multiple linear regression analysis using SPSS software version 22. This research prove that Solvency has a positive significant effect on audit report lag. whereas Firm Size, Profitability, and KAP Reputation have a significantly negative influence on audit report lag.